An efficient method for the preparation of tert-butyl esters from benzyl cyanide and tert-butyl hydroperoxide under the metal free condition. Issue 104 (26th October 2016) - Chen, Xiuling; Li, Yan; Wu, Minghu; Guo, Haibing; Jiang, Longqiang; Wang, Jian; Sun, Shaofa
Abstract : A novel protocol to synthesize tert -butyl esters from benzyl cyanides and tert -butyl hydroperoxide has been successfully achieved. Csp 3 –H bond oxidation, C–CN bond cleavage and C–O bond formation proceeded smoothly in one pot under the metal-free condition. Abstract : A novel protocol to synthesize tert -butyl esters from benzyl cyanides and tert -butyl hydroperoxide has been successfully achieved. In the presence of tert -butyl hydroperoxide, Csp 3 –H bond oxidation, C–CN bond cleavage and C–O bond formation proceeded smoothly in one pot under the metal-free condition.